2017
DOI: 10.1037/bne0000182
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in heart failure: A protective role for angiotensin-(1-7).

Abstract: Patients with congestive heart failure (CHF) have increased hospital readmission rates and mortality if they are concomitantly diagnosed with cognitive decline and memory loss. Accordingly, we developed a preclinical model of CHF-induced cognitive impairment with the goal of developing novel protective therapies against CHF related cognitive decline. CHF was induced by ligation of the left coronary artery to instigate a myocardial infarction (MI). By 4- and 8-weeks post-MI, CHF mice had approximately a 50% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 88 publications
(105 reference statements)
7
46
0
Order By: Relevance
“…Thus, the time-dependent differences in microglial derami cation and pro-in ammatory markers between the PVN and the amygdala are in line with the fact that sympathohumoral and cardiovascular manifestations in HF precede the mood and cognitive de cits associated with this disease (58,80,81). HF-induced cognitive impairments in both rats and mice has been previously described (82,83) and while it is well established that the PVN is a main neuronal substrate contributing to mood regulation, our studies provide an indirect evidence that neuroin ammation within the amygdala may constitute a neuronal substrate contributing to HF-induced mood de cits. A recent study showed that the microglia inhibitor minocycline improved depression-like behavior in HF rats (84).…”
Section: Discussionsupporting
confidence: 59%
“…Thus, the time-dependent differences in microglial derami cation and pro-in ammatory markers between the PVN and the amygdala are in line with the fact that sympathohumoral and cardiovascular manifestations in HF precede the mood and cognitive de cits associated with this disease (58,80,81). HF-induced cognitive impairments in both rats and mice has been previously described (82,83) and while it is well established that the PVN is a main neuronal substrate contributing to mood regulation, our studies provide an indirect evidence that neuroin ammation within the amygdala may constitute a neuronal substrate contributing to HF-induced mood de cits. A recent study showed that the microglia inhibitor minocycline improved depression-like behavior in HF rats (84).…”
Section: Discussionsupporting
confidence: 59%
“…The peptide angiotensin-(1-7) (Ang-1-7) meets these criteria. Ang-(1-7) is known to decrease brain ROS production and inflammation in preclinical models of HF (Hay et al, 2017), to increase cerebral blood flow (Zimmerman et al, 2002;Jiang et al, 2014), and to be safe in clinical studies in humans (Rodgers et al, 2006). Within the brain, the Mas receptor (MasR) is found on neurons, microglia, and vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of MasR decreases ROS and brain inflammation, increases cerebral circulation via increases in endothelial nitric oxide release and inhibition of inflammatory cytokines, and inhibits hypoxia-inducing factor-1a (Ferrario, 2006;Zheng et al, 2014;Chang et al, 2016;Salminen et al, 2017). Because the MasR is found in high quantities within the hippocampus and perirhinal cortex as well as in vascular endothelial cells, Ang-(1-7) is hypothesized to be effective in targeting memory impairments related to hypoxia and inflammation-related neurodegenerative disease (Hay et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the time-dependent differences in microglial cell activation and pro-inflammatory markers between the PVN and the amygdala are in line with the fact sympathohumoral and cardiovascular manifestations in HF precede the mood and cognitive deficits associated with this disease (58,80,81). HF-induced cognitive impairments in both rats and mice have been extensively studied (82,83) and while it is well established that the PVN is a main neuronal substrate contributing to mood regulation, our studies provide an indirect evidence that NI within the amygdala may constitute a neuronal substrate contributing to HF-induced mood deficits. A recent study showed that the microglia inhibitor minocycline improved depression-like behavior in HF rats (84).…”
Section: Region-specific Differences and Time-dependency Of Heart Faimentioning
confidence: 76%